2017
DOI: 10.1055/s-0043-116660
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tissue Stiffness Using Shear Wave Elastography in Men with Normal Testicular Tissue, Testicular Microlithiasis and Testicular Cancer

Abstract: Objectives To compare elastography measurements in men with normal testicular tissue, testicular microlithiasis and testicular cancer. Methods A total of 248 consecutive patients were included. All men provided written informed consent. Testicular stiffness was assessed using shear wave elastography (SWE). Three SWE velocity measurements were assessed in each testicle. The patients were divided into three groups; men with normal testicular tissue (n=130), men with testicular microlithiasis (n=99) and men with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
0
20
1
Order By: Relevance
“…There is limited information regarding the use of SWE in the evaluation of testicular lesions. Investigation of the role of SWE in the overall assessment of background parenchyma has suggested that values may be elevated in the case of testicular microlithiasis [386], infertility [387], undescended testis [388]. It also has the potential to differentiate seminomas from non-seminomatous lesions [389] and has been evaluated in burnt-out tumors [390].…”
Section: Swementioning
confidence: 99%
“…There is limited information regarding the use of SWE in the evaluation of testicular lesions. Investigation of the role of SWE in the overall assessment of background parenchyma has suggested that values may be elevated in the case of testicular microlithiasis [386], infertility [387], undescended testis [388]. It also has the potential to differentiate seminomas from non-seminomatous lesions [389] and has been evaluated in burnt-out tumors [390].…”
Section: Swementioning
confidence: 99%
“…The stiffness of testicular cancer can be more than double the stiffness of normal testis, suggesting that increased stiffness could be used as a testicular malignancy marker, and detectable by ultrasound elastography 188 , 189 . In testicular microlithiasis, a modest increase of tissue stiffness compared to normal testicles was measured by SWE 188 , but no malignant characteristics are measured by SWE or MRI diffusion in this condition (stiffness values reported in Table 2 ) 189 . Thus, benign testicular lesions can be differentiated from malignant ones both by MRI diffusion and elastography.…”
Section: Organ-specific Stiffnessmentioning
confidence: 99%
“…This is known as a 3-ring structure [7]. Mean shear wave velocities of 0.76 m/sec (95% confidence interval, 0.75 to 0.78 m/sec) from 130 normal testicles and 1.92 m/sec in 19 patients with testicular cancer have been reported by Pedersen et al [8] and Marcon et al [9], respectively, both using virtual touch tissue imaging quantification (VTIQ; Siemens Medical Solutions, Mountain View, CA, USA). Furthermore, Trottmann et al [11] reported that the center of the testis showed significantly lower shear wave velocity than the inferior and superior portion of the testis, through results obtained from 60 healthy testes using SuperSonic Imaging (Aixplorer, Paris, France).…”
Section: Normal Testesmentioning
confidence: 99%
“…A shear wave elasticity value of 1.7 kPa using the SuperSonic Imagine apparatus (Aixplorer Provence) was described in a case report of a segmental testicular infarction, compared to an elasticity value of 2.6 kPa in the adjacent normal testicular parenchyma [31]. A study of 248 patients including 130 with normal testicular tissue, 99 with microlithiasis, and 19 with testicular cancer showed that the mean shear wave velocity from three measurements taken from the centre, upper pole, and lower pole of the testis or testicular lesion was significantly higher in patients with testicular cancer (mean velocity, 1.92 m/sec) than in those with normal testicular tissue (0.76 m/sec) or testicular microlithiasis (0.79 m/sec) [8].…”
Section: Testicular Non-neoplastic Lesionsmentioning
confidence: 99%